A new variety and a review of Nervilia (Orchidaceae) in Taiwan - Zeng, Sin-Yuan; Wang, Yi-Tse; Liu, Ching-Hwang; Lee, Yung-I; Lin, Tsan-Piao (Phytotaxa, 2025)
Nervilia taitoensis var. parviflora, a new orchid variety of Taiwan, is described and illustrated. A brief taxonomical review of species and a dichotomous key for Nervilia in Taiwan are presented. Also, an appraisal of the Nervilia phylogeny and species complex is discussed.